Global Cardiovascular Risk Assessment in the Management of Primary Hypertension: The Role of the Kidney - Francesca Viazzi; Giovanna Leoncini; Roberto Pontremoli (International Journal of Hypertension)
The knowledge of each patient’s global risk profile is a prerequisite for effective therapeutic strategies in primary hypertension. Detecting the presence of subclinical organ damage at the cardiac, vascular, and renal levels is key for stratifying cardiovascular risk and may also be helpful in choosing antihypertensive agents and in monitoring the effectiveness of treatment. A systematic, in-depth search for subclinical organ damage, however, may be difficult to carry out because of logistic and economic problems related to the high prevalence of hypertension in the population. Renal abnormalities such as microalbuminuria and reduction in glomerular filtration rate have proven to be powerful predictors of cardiovascular and renal outcome. Thanks to their relatively low cost and wide applicability, more widespread use of these tests in the diagnostic workup will help detect subsets of patients at greater risk for whom additional preventive and therapeutic treatment is advisable.